The Impact of Social Capital on Overcoming Systemic Barriers and Lack of Benefit of the Doubt for Black Women in Leadership: Insights from Kamala Harris’s Presidential Campaign - Jennifer R. Bishop (Business Ethics and Leadership)
Black women in America continue to face formidable barriers in the pursuit of leadership roles, encountering both racial and gender-based systemic obstacles that deny them the benefit of the doubt, limit their access to influential networks and limit opportunities for career advancement to top executive leadership positions. Unlike their white counterparts, Black women seldom experience the privilege of being seen as “neutral” or “qualified” without added scrutiny, making their journey to leadership fraught with challenges. Resilience, the capacity to adapt and persist in adversity, is crucial in navigating these challenges. Kamala Harris’s 2024 presidential campaign exemplifies these barriers. Despite her qualifications, Harris lost to a white male opponent with a criminal record, highlighting systemic biases. Supported by the “Win With Black Women” initiative, Harris’s campaign relied on social capital and resilience to counteract entrenched prejudice. However, the limitations of social capital alone underscore the need for systemic change. This paper uses social capital theory and the newly proposed benefit of the doubt (BoD) theory to examine how Black women leverage networks and resilience to navigate barriers, highlighting the structural privileges that disadvantage them. A conceptual framework model that highlights the pathways through which social capital, BoD denial, and organizational evaluation practices intersect, impacting leadership opportunities for Black women, is included to visually demonstrate these dynamics and the interaction of key constructs in the leadership trajectory of Black women.